Student’s technical competencies: Analysis for Palestine Technical University – Kadoorie - shehadeh, sonia (Journal of Technical Education and Training, 2025)
The study aimed to investigate the Student’s technical competencies level at Palestine Technical University – Kadoorie, and examined the role of variables gender, place of residence, degree, collage, and academic level. The descriptive approach used. A questionnaire consisting of (15) items used. The population of the study consisted of all (2300) students at PTUK/ Ramallah Branch at the second semester of the academic year 2024-2025, a (25%) random sample was selected a made up of (575) students, The results showed that the total score for the Technical applied competencies domain was the highest with a mean of (3.86), It also showed that there were no statistically significant differences due to place of residence variable, however, it reveals that there were statistically significant differences due to gender variable in favored for female students, due to Collage variable in the Digital communication competencies domains between Computer science and Business Management students in favoured Computer science students, in the Digital communication competencies domain between Computer science and Media students in favoured Media students. Due to academic level variable in all domains between first year and fourth year students in favoured forth year students. The study suggests that the university should Integrate digital competencies across curricula, Promote gender-balanced digital education, Enhance digital competencies for diploma programs, Support discipline-specific digital skill development, Facilitate progressive digital learning, and Continuous evaluation and improvement.